Ethics briefings - Chrispin, E. (Journal of medical ethics, 2009)
In February 2009, compulsion in relation to childhood vaccination was the focus of renewed public debate in the UK. The publication of data from the Health Protection Agency showed that in 2008 there were 1 348 confirmed cases of measles in England and Wales. This was the highest number reported since the monitoring scheme began in 1995,1 signalling a dramatic increase in the number of cases, which had been fewer than 200 each year between 1996 and 2000.2 The agency reported that most of the 2008 cases had been in children not fully vaccinated with the combined measles, mumps and rubella (MMR) vaccine and therefore could have been prevented.3Uptake of the MMR vaccine in the UK has declined since 1998, following widespread media coverage of since-discredited research on the risks of the vaccine.4 Although uptake has risen more recently (across the UK in February 2009, 84.5% of 2-year-olds had been immunised with their first dose of MMR), by age 5 years, when children are recommended to have a second dose, it was just 77.9%.1 In order to achieve population immunity from measles, whereby immunisation rates in a population are sufficiently high that the unvaccinated are also protected, 95% of the population must be immune.5 The reported vaccination levels for the UK therefore indicated that the whole unvaccinated population is vulnerable.All immunisations in the UK, including those for MMR, are voluntary, although incentives are given to health professionals to achieve immunisation targets. It is argued by some that the introduction of a quasi-mandatory system could increase the number of those immunised and help achieve population immunity.6 Under this approach, individuals are required to be vaccinated unless they qualify for exemption, and if they refuse are subject to possible penalties. The idea has been …